Enhancing good governance and fraud prevention for school performance - Sri Rahayu; Yudi; Sofyan; Rahayu; Salman Jumaili (Cogent Business & Management)
This study aims to enhance good governance and fraud prevention as key drivers for improving school performance. Using a mixed methods approach, the research collected quantitative data from 271 respondents through structured surveys, supported by qualitative insights gathered from in-depth interviews and focus group discussions. The quantitative analysis, conducted using Smart-PLS, revealed that both good governance and fraud prevention have a significant and positive influence on school performance. In contrast, organizational commitment was not found to significantly affect either of these variables, nor did it have an indirect impact on performance. Qualitative findings suggest that this limited effect may be linked to the employment conditions of contract-based staff, where uncertainty surrounding job status undermines motivation and long-term commitment. Alongside its empirical analysis, the study offers a practical fraud prevention framework specifically adapted for school environments. The model emphasizes early risk detection, inclusive stakeholder participation, and collaborative oversight mechanisms. By bridging theoretical frameworks with real school governance challenges, this study offers meaningful contributions for researchers and policymakers seeking to foster a culture of integrity and enhance performance in the education sector.